2006
DOI: 10.1105/tpc.105.040774
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Nature of Sphingolipids in Plants as Revealed by the Functional Identification and Characterization of theArabidopsisLCB1 Subunit of Serine Palmitoyltransferase

Abstract: Serine palmitoyltransferase (SPT) catalyzes the first step of sphingolipid biosynthesis. In yeast and mammalian cells, SPT is a heterodimer that consists of LCB1 and LCB2 subunits, which together form the active site of this enzyme. We show that the predicted gene for Arabidopsis thaliana LCB1 encodes a genuine subunit of SPT that rescues the sphingolipid long-chain base auxotrophy of Saccharomyces cerevisiae SPT mutants when coexpressed with Arabidopsis LCB2. In addition, homozygous T-DNA insertion mutants fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
179
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 69 publications
18
179
0
Order By: Relevance
“…The lcb1 mutations caused a substantially reduced level of the LCB2 protein in both a Chinese hamster ovary cell mutant line [43] and yeast cells [44], thus leading to lethality in both cases. Similarly, the lcb1-1 mutation causes an embryolethal phenotype, indicating an essential role of FBR11 in plant growth and development [41]. However, a striking phenotype of fbr11-1 appears to be its resistance to FB 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lcb1 mutations caused a substantially reduced level of the LCB2 protein in both a Chinese hamster ovary cell mutant line [43] and yeast cells [44], thus leading to lethality in both cases. Similarly, the lcb1-1 mutation causes an embryolethal phenotype, indicating an essential role of FBR11 in plant growth and development [41]. However, a striking phenotype of fbr11-1 appears to be its resistance to FB 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Sequence comparison revealed that FBR11 encodes a putative LCB1 subunit of SPT, catalyzing the formation of 3-ketosphinganine during sphingolipid de novo synthesis (Figure 4). During the course of this study, Chen et al [41] reported the characterization of LCB1/FBR11. Coexpression of LCB1/FBR11 and LCB2 cDNA was able to complement the long-chain base auxotrophy of S. cerevisiae lcb1∆ and lcb2∆ single and double mutants, indicating that both LCB1 and LCB2 are functional subunits of SPT.…”
Section: Fbr11 Encodes An Lcb1 Subunit Of Serine Palmitoyltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…SPT synthesizes LCBs, unique components of sphingolipids, by catalyzing a pyridoxal phosphate-dependent condensation of Ser and palmitoyl (16:0)-CoA in plants (Markham et al, 2013). Similar to other eukaryotes, the Arabidopsis (Arabidopsis thaliana) SPT is a heterodimer consisting of LCB1 and LCB2 subunits (Chen et al, 2006;Dietrich et al, 2008;Teng et al, 2008). Research to date has shown that SPT is regulated primarily by posttranslational mechanisms involving physical interactions with noncatalytic, membrane-associated proteins that confer positive and negative regulation of SPT activity (Han et al, 2009Breslow et al, 2010).…”
mentioning
confidence: 99%
“…In plants, the maintenance of sphingolipid homeostasis is vital to ensure sufficient sphingolipids for growth (Chen et al, 2006;Kimberlin et al, 2013) while restricting the accumulation of PCD-inducing ceramides and LCBs until required for processes such as the pathogen-triggered hypersensitive response. Serine palmitoyltransferase (SPT), which catalyzes the first step in LCB synthesis, is generally believed to be the primary control point for sphingolipid homeostasis (Hanada, 2003).…”
mentioning
confidence: 99%